Design of specific inhibitors of quinolinate synthase based on [4Fe–4S] cluster coordination12. Issue 26 (11th March 2019) - Saez Cabodevilla, Jaione; Volbeda, Anne; Hamelin, Olivier; Latour, Jean-Marc; Gigarel, Océane; Clémancey, Martin; Darnault, Claudine; Reichmann, Debora; Amara, Patricia; Fontecilla-Camps, Juan C.; Ollagnier de Choudens, Sandrine
Abstract : A multidisciplinary approach allowed to identify specific inhibitors of quinolinate synthase, a [4Fe–4S]-containing enzyme involved in the formation of quinolinic acid and their action mode. Abstract : Quinolinate synthase (NadA) is a [4Fe–4S] cluster-containing enzyme involved in the formation of quinolinic acid, the precursor of the essential NAD coenzyme. Here, we report the synthesis and activity of derivatives of the first inhibitor of NadA. Using multidisciplinary approaches we have investigated their action mechanism and discovered additional specific inhibitors of this enzyme.